Optimalisasi Pemanfaatan Website Sebagai Media Cyber Public Relations (Studi Kasus Pada PT. Indonesian Technology Kota Metro) - Anggewa, Dava; Pienrasmi, Hanindyalaila; Waskito, Budhi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to analyze the optimization of website utilization as a cyber public relations (CPR) medium in supporting the company's communication strategy, with a case study at PT. Indonesian Technology, Kota Metro. The research approach used is qualitative with a case study method. Data collection was carried out through in-depth interviews, participatory observation, and documentation. The research findings show that the company's website has been utilized as a cyber PR medium; however, it still requires improvement in aspects such as interactivity, the application of search engine optimization (SEO) techniques, as well as the consistency and quality of information presentation. An effective digital communication strategy plays a crucial role in increasing stakeholder interest in the company. The conclusion of this study emphasizes that optimizing a website as a cyber public relations (CPR) medium must include the delivery of high-quality content, systematic implementation of SEO, and a digital-based interaction strategy to strengthen corporate communication.